PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA ROCKET CHICKEN - Afandi, Adinda Cornellya; Anggraeni, Rila (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
For companies operating in the culinary field, customer satisfaction is inseparable from improving product quality and service quality. Product quality is an important thing that must be sought by companies if they want the products produced to be able to compete in the market. The objective of this explanatory research is to identify the effect of product and service quality on the satisfaction of Rocket Chicken’s consumer in Gringging, Kediri. This type of research is explanatory research. Using non-probability method with purposive sampling technique, 160 people with the minimum age of 13 years living around Gringging village of Grogol sub-district in Kediri regency and having visited the restaurant at least twice were selected as the respondents. This research uses primary data obtained from 5-point Likert scale questionnaires distributed to the respondents. Utilizing multiple linear regression performed in SPSS ver. 24, this study finds that product and service quality significantly influence consumer satisfaction.